Transition‐Metal‐Free Regioselective Alkylation of Quinoline N‐Oxides via Oxidative Alkyl Migration and C−C Bond Cleavage of tert‐/sec‐Alcohols. Issue 5 (5th January 2018) - Sen, Chiranjit; Ghosh, Subhash C.
Abstract: An unprecedented C2‐alkylation of quinoline N‐oxide derivatives via C−C bond activation of tert‐ and sec ‐alkyl alcohol is described using hypervalent iodine (III) reagent PhI(OAc)2 (PIDA). This regioselective alkylation using mild hypervalent iodine reagents is more practical, operationally simple and transition metal free. The reaction proceeds efficiently with a broad range of substrates including quinoline, isoquinoline, and pyridine N‐oxides using a variety of tert ‐/ sec ‐ alcohols. From experimental outcome, we also propose a rationalized mechanism, mediated by PIDA. Abstract :